The ERK1/2 Inhibitor U0126 Attenuates Diabetes-Induced Upregulation of MMP-9 and Biomarkers of Inflammation in the Retina - Ghulam Mohammad; Mohammad Mairaj Siddiquei; Mohammad Imtiaz Nawaz; Ahmed M. Abu El-Asrar (Journal of Diabetes Research)
This study was conducted to determine the expression of matrix metalloproteinase-9 (MMP-9) and tissue inhibitor of metalloproteinase-1 (TIMP-1) in a time-dependent manner and the effect of extracellular-signal-regulated kinases-1/2 (ERK1/2) inhibition on the expressions of MMP-9, TIMP-1, and inflammatory biomarkers in the retinas of diabetic rats. The expression of MMP-9 was quantified by zymography, and the mRNA level of MMP-9 and TIMP-1 was quantified by RT-PCR. The expression of inducible nitric oxide synthase (iNOS), interleukin-6 (IL-6), and tumor necrosis factor-alpha (TNF-α) was examined by Western blot analysis. MMP-9 expression was significantly higher in diabetic rat retinas compared to controls at all time points.TIMP-1 expression was nonsignificantly upregulated at 1week of diabetes and was significantly downregulated at 4 and 12 weeks of diabetes. Intravitreal administration of the ERK1/2 inhibitor U0126 prior to induction of diabetes decreased ERK1/2 activation, attenuated diabetes-induced upregulation of MMP-9, iNOS, IL-6, and TNF-α and upregulated TIMP-1 expression. In MMP-9 knockout mice, diabetes had no effect on retinal iNOS expression and its level remained unchanged. These data provide evidence that ERK1/2 signaling pathway is involved in MMP-9, iNOS, IL-6, and TNF-α induction in diabetic retinas and suggest that ERK1/2 can be a novel therapeutic target in diabetic retinopathy.